PENGUATAN TAMAN WISATA ALAM “SENDANG BULUS”, DESA PAGER, BUNGKAL, PONOROGO BERBASIS ESTETIK YANG INSTAGRAMABLE - Heriana, Tutik; Prihatin, Lilik; Fauzi, Ferry; Bilyastuti, Mai Puspadyna; Suryanto, Agus; Sugeng, Sugeng; Sholeh, Mohammad Hasyim; Nurkharisma, Aditya (Universitas Mataram, 2024)
The “Sendang Bulus” tourist park is one of the interesting and natural tourist destinations. This park is famous for the presence of bulus (Pig-snouted Turtle) and its natural beauty which attracts visitors. To increase the attractiveness of the Sendang Bulus tourist park, the service team conducted a survey and observation at the location, where an important finding was obtained: the need for aesthetic and instagramable photo spots as a means of promoting the tourist park. The purpose of the service is to make the Sendang Bulus tourist park more aesthetic and instgaramabale, so that it can further increase tourist attractiveness to attract visitors to enliven the Sendang Bulus tourist park. The activity methods used in the service are interviews, observation, documentation, planning, activity implementation, activity evaluation. In developing this tourist park, the service team carried out various activities ranging from making pergola arch photo spots decorated with acrylic letters “Sendang Bulus” with aesthetic decorative garden chairs in front of them, making photo spots from dead trees decorated with synthetic leaves and fruits, to installing aesthetic solar decorative garden lights. The added value is expected to provide a positive correlation to tourist visits due to the easier promotion of the name Sendang Bulus to the outside world with the existence of attractive, aesthetic and instagramable photo spots.